Collective forgiving - Hamilton, Kelly (Rhodes University, Faculty of Humanities, Department of Philosophy, 2009)
Forgiveness is traditionally understood as a personal change of heart, in which an individual victim of a wrongdoing overcomes her resentment towards the perpetrator of that wrongdoing. Peter Strawson (1974) famously argued that resentment is a personal participant retributive reactive attitude, and the overcoming of such an attitude through forgiveness is itself a personal reactive attitude "“ in other words, forgiveness is an affective response to a wrongdoing by an individual victim, that is devoid of a retributive element. Because reactive attitudes are personal, it is argued that collectives "“ groups of individuals "“ cannot forgive, since collectives cannot, as collectives, hold reactive attitudes. I argue against this. I show that it is possible for collectives to hold attitudes in a way that is not reducible to individuals holding attitudes as individuals, and yet these attitudes still remain personal. Individuals exist within communities, and are interdependent on one another. Much of an individual"Ÿs beliefs and attitudes depend on the collectives that she is a part of. I argue that an attitude is collective when it is deemed to be the appropriate attitude for members of the collective to hold. Members of the collective will take this attitude on as their own insofar as they identify themselves as members of the collective. Individuals hold the attitude, making the attitude personal, but since the individuals hold the attitude in virtue of their membership to a collective, the attitude is also collective. Given that forgiveness is itself a reactive attitude, and that collectives can hold attitudes, I argue that it is possible for a collective to forgive. Members of a collective will come to forgive when forgiveness is held up as the appropriate attitude for them, and once enough members have taken on the attitude of forgiveness as their own attitude, a collective can be said to have forgiven.
Keywords: Forgiveness -- Philosophy; Collective behavior -- Philosophy; Retribution -- Philosophy; Reconciliation -- Philosophy